Caracterização litoestratigráfica e paleontológica do Membro Boacica da Formação Batinga, Neocarbonífero da bacia de Sergipe-Alagoas - Farias, Ricardo Monteiro (2013)
The Boacica Member of the Batinga Formation, in the Sergipe-Alagoas basin, occurs on the high structural Japoatã (SE), Penedo and Palmeira Alta (AL), characterized by rhythmic intercalation of laminated siltstones, shales and very fine sandstones, assigned to a system depositional deltaics fronts and prodeltas. Despite very poor fossiliferous content, some analyzes recovered palynomorphs characteristic from the Eo Mesopennsylvanian (Neocarboniferous), and some levels are locally abundant ichnofossils. Ichnological associations are poorly diversified, represented by traces of rest or locomotion. The discovery of trace fossils associated with the emergence of new outcrops, allowed the new studies lithostratigraphic and paleontological detailed in this unit. This study had to perform the characterization lithostratigraphic and paleontological in two outcrops of this unit, Batinga 5 and Pescocinho 3. The sections are characterized by rhythmic intercalations of shales, siltstones laminated and massives of whitish gray color, with very fine sandstones cream colored, sometimes showing cyclical patterns of coarsening upward prays fining upward reflecting changes in the depositional process. The sandstones generally show structures climbing-ripples. According to the stratigraphic succession raised in these outcrops, eight sedimentary facies were observed, confirming that the deposits of facies suggest prodelta, delta front, turbidite lobes, lake bottom, fluvial, crevasses and the debris englaciais. The ichnofossils were observed along some facies and analyzed in different lithologies (shales, siltstones and sandstones) but are not as abundant in Batinga 5. The ichnofossils presented themselves as bioturbation structures, featuring brands resting, locomotion and pasture. Traces are reduced sizes and present as bilobates thrails, straight or curved, oval, in a "coffee beans" form and other tracks irregular with random crossing. The traces were classified as belonging to the ichnospecie Isopodichnus problematica Schindewolf, 1921 and ichnogenus Rusophycus Hall, 1852, Helminthoidichnites Fitch, 1850, Aulichnites Fenton & Fenton, 1937, are more common in siltstones and shales. The ichnospecie Paganzichnus carboniferus Pazos, 2000 together with ichnogenus Gordia Emmons, 1844 and Scoyenia White, 1929, are more common in sandy prodeltaic facies, although also found in siltstones-shale facies. Probably these traces were generated by activities of the arthropods, branchiopods crustaceans and organisms nematomorph. It was also verified that one morphotype was named as Morphotype A . This morphotype displays small short lines with elongated shapes, with a straight path to curve slightly, with differents directions and is preserved in convex hyporelief or concave epirelief both being frequent in muddy facies prodeltaics as in sandy facies of deltaic front. The association of the traces studied here features a subaqueous environment, muddy, shallow and relatively calm may represent the ichnofacies Mermia (lake) and Scoyenia (transitional).